Extraretinal Light Perception in the Sparrow, III: The Eyes Do Not Participate in Photoperiodic Photoreception - Menaker, Michael (1970)
Photoperiodic control of testis growth in Passer domesticus (house sparrow) is mediated entirely by extraretinal photoreceptors in the brain. The eyes do not participate in photoperiodically significant photoreception. Removal of the pineal organ does not affect either the response to light or, to a first approximation, the process of recrudescence. The intensity of light reaching the retina and that reaching the extraretinal photoreceptor were varied independently. This technique will make it possible to study brain photoreception in species of birds that will not tolerate blinding. Extreme caution is necessary in the interpretation of brain lesion experiments in which reproductive function is modified, since photoreception by brain receptors of unknown anatomical location affects testicular state.